KEANEKARAGAMAN POHON DAN POLE SERTA POTENSI KARBON TERSIMPAN DI KAWASAN HUTAN SEKUNDER 30 TAHUN DAN PERKEBUNAN KOPI DI TELAGAH, LANGKAT - Jhon Marthali Simamora; Retno Widhiastuti; Nursahara Pasaribu (Saintia Biologi, 2013)
The diversity of tree, pole and potential of carbon stored in 30 years secondary forest and coffee field at Telagah District of Langkat was investigated from February to June 2012. The  study site was determined by purposive sampling method with total area 40 x 200 meters. The study site is divided into 20 plots and sub plots. Result found that 15 families and 23 species for tree phase and 16 families and 26 species of pole phase. The area were dominated by Macaranga tanaria with important value 57.11% for tree, and followed by Ficus aurantiacea with important value 54. 472% for pole. The diversity index of tree is 2.650 and 2.715 for pole. Equitability index of tree is 0.520 and 0.586 for pole. The potential of carbon stored in tree is 146.519 ton/ha, 3.933 ton/ha for pole, and 0.0489 ton/ha for coffee plantation.   Keywords: Carbon, Coffee Plantation, Diversity, Important value index, pole, purposive sampling